2 - Quality Issues in Kenya’s Higher Education Institutions - Marwa, Simmy M.; Kagondu, Rosemary (Journal of Higher Education in Africa, 2022)
The capability of higher education institutions (HEIs) to serve as drivers of economic competitiveness is reducing in different developing countries due to numerous constraints which interfere with their quality. This article empirically investigated the quality assurance practices in Kenya’s HEIs, efficacy of the frameworks used, gaps and opportunities for improvement. Perceptions on eight dimensions of quality, namely, governance and management, programme planning and management, curriculum development, teaching and learning, infrastructure, assessment, research, publication and innovation and programme results were sought from three categories of respondents in eight universities.Data were collected from a sample of 136 academic staff, 340 students, and 34 staff of quality assurance directorates out of a total of 222,384, and 38 targeted respondents respectively. A 7 point Likert scale: questionnaire (ranging from 1= Strongly Disagree to 7 = Strongly Agree) was administered. The quantitative data was corroborated through interviewing the three respondent groups in the study. Analysis of gaps depicted by the differences in the weighted averages of responses of staff of quality assurance directorates and academic staff, staff of quality assurance directorates and students, and academic staff and students was done. Each HEI was first analysed individually and then findings were consolidated to obtain the overall gap on each quality dimension studied across all participating HEIs. Results indicated revealed gaps in each of the eight dimensions of quality investigated and showed Kenya’s HEIs were at different levels on the quality continuum. Hence as the results are suggestive of room for improvement, HEIs have the opportunity to benchmark with local HEIs that have progressed on certain parameters of quality and, evolve homegrown models of best practice. This will enable these institutions to continuously improve their positioning on the quality continuum which is a key tenet of quality management. The most challenged dimension was research and publication. The research recommends that Commission for University Education (CUE) should strengthen accountability mechanisms in the HEIs. It brings to the fore the need for HEIs to develop and strengthen their collaborations and networks between themselves and with industry.